The Effectiveness Of Liquefied Organic Fertilizer (LOF) Market Waste On Increased Growth and Red-Spinach Production (Amarathus tricolor. L) - Lengkong, Edy F.; Malintoi, Friska; Najoan, Jemmy; Paat, Frangky J.; Ogie, Tommy B.; Nangoi, Ronny (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2022)
Abstract. Edy Lengkong1*, Friska Malintoi 1, Jemmy Najoan1, Frangky J. Paat1, Tommy B. Ogie1, , Ronny Nangoi1. The Effectiveness Of Liquefied Organic Fertilizer (LOF) Market Waste On Increased Growth and Red-Spinach Production (Amarathus tricolor. L). Ekoton 11. 44-6. Red spinach (Amarathus tricolor L.) is a commodity that has very high development, it is proven that the number of requests tends to increase. Not inferior to other horticultural crops, red spinach plants have a fairly high economic value. Apart from being consumed every time, red spinach also contains nutrients needed by the body (Irwan et al., 2005). According to the Central Statistics Agency (BPS) in 2017, the total harvested area of ​​spinach in Indonesia in 2017 reached 40,608 hectares with a production of 160,248 tons ranks 9th out of 18 commercial vegetables cultivated and produced in Indonesia. There are 3 traditional markets in Manado City, namely Bahu Market in Malalayang District, Karombasan Market in Wanea District, and Bersehati Market in Wenang District. Can giving market waste POC affect the growth and yield of red spinach? The purpose of this study was to determine the effectiveness of giving market waste POC to the growth and yield of red spinach. And knowing the best POC concentration for the growth and yield of red spinach. It is hoped that this research can provide information on the use of market waste as a source of nutrients for the growth and yield of red spinach in the form of liquid organic fertilizer (POC). This research was arranged using a Randomized Block Design (RAK) with 5 treatments of POC concentration of market waste on red spinach plants. P0: control, P1: 25%, P2: 50%, P3: 75%, P4:100%. Each treatment consisted of 5 plant samples and was repeated 3 times to obtain 75 samples. Market waste POC with a concentration of 75% is the best concentration on the variable height of red spinach plants. Keywords: POC, Red Spinach, Market Garbage